EFEKTIVITAS PENGGUNAAN MULTIKOM TERHADAP PENINGKATAN KETERAMPILAN TEKNIK REBOZO PESERTA DIDIK SARJANA TERAPAN KEBIDANAN POLITEKNIK BHAKTIASIH - Dewi Sulastri Sutaran; Hidayat Wijayanegara; Yanti Herawati; Teni Nurlatifah; Ma’mun Sutisna; Herry S Sastramihardja (JOMIS (Journal of Midwifery Science), 2025)
Introduction:Labor pain can affect maternal physiology by increasing blood pressure, heart rate, respiratory rate, and muscle tension, which may interfere with concentration during childbirth. The rebozo technique is a non-pharmacological method used to reduce labor pain, yet its implementation in midwifery education remains limited. Methods: This quasi-experimental study employed a two-group pretest-posttest control design, involving 76 seventh-semester midwifery students randomly assigned to either an intervention group (n = 38), which used D’ Multikom interactive multimedia, or a control group (n = 38), which used a conventional practical guidebook. Skills were assessed before and after the intervention using a checklist. The Mann-Whitney test was used for data analysis, and effectiveness was evaluated using the WebQual 4.0 instrument. Results:The results showed a statistically significant improvement in rebozo technique skills in the intervention group compared to the control group (p = 0.001). The effectiveness score of D’ Multikom reached 89.84%, categorized as highly effective. Conclusion: D’ Multikom is more effective than traditional guidebooks in improving midwifery students’ practical skills in the rebozo technique and is recommended as an innovative learning tool in midwifery education.